If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 = 5q(3q + -10) + -5q Reorder the terms: -15 = 5q(-10 + 3q) + -5q -15 = (-10 * 5q + 3q * 5q) + -5q -15 = (-50q + 15q2) + -5q Reorder the terms: -15 = -50q + -5q + 15q2 Combine like terms: -50q + -5q = -55q -15 = -55q + 15q2 Solving -15 = -55q + 15q2 Solving for variable 'q'. Reorder the terms: -15 + 55q + -15q2 = -55q + 55q + 15q2 + -15q2 Combine like terms: -55q + 55q = 0 -15 + 55q + -15q2 = 0 + 15q2 + -15q2 -15 + 55q + -15q2 = 15q2 + -15q2 Combine like terms: 15q2 + -15q2 = 0 -15 + 55q + -15q2 = 0 Factor out the Greatest Common Factor (GCF), '5'. 5(-3 + 11q + -3q2) = 0 Ignore the factor 5.Subproblem 1
Set the factor '(-3 + 11q + -3q2)' equal to zero and attempt to solve: Simplifying -3 + 11q + -3q2 = 0 Solving -3 + 11q + -3q2 = 0 Begin completing the square. Divide all terms by -3 the coefficient of the squared term: Divide each side by '-3'. 1 + -3.666666667q + q2 = 0 Move the constant term to the right: Add '-1' to each side of the equation. 1 + -3.666666667q + -1 + q2 = 0 + -1 Reorder the terms: 1 + -1 + -3.666666667q + q2 = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -3.666666667q + q2 = 0 + -1 -3.666666667q + q2 = 0 + -1 Combine like terms: 0 + -1 = -1 -3.666666667q + q2 = -1 The q term is -3.666666667q. Take half its coefficient (-1.833333334). Square it (3.361111114) and add it to both sides. Add '3.361111114' to each side of the equation. -3.666666667q + 3.361111114 + q2 = -1 + 3.361111114 Reorder the terms: 3.361111114 + -3.666666667q + q2 = -1 + 3.361111114 Combine like terms: -1 + 3.361111114 = 2.361111114 3.361111114 + -3.666666667q + q2 = 2.361111114 Factor a perfect square on the left side: (q + -1.833333334)(q + -1.833333334) = 2.361111114 Calculate the square root of the right side: 1.536590744 Break this problem into two subproblems by setting (q + -1.833333334) equal to 1.536590744 and -1.536590744.Subproblem 1
q + -1.833333334 = 1.536590744 Simplifying q + -1.833333334 = 1.536590744 Reorder the terms: -1.833333334 + q = 1.536590744 Solving -1.833333334 + q = 1.536590744 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '1.833333334' to each side of the equation. -1.833333334 + 1.833333334 + q = 1.536590744 + 1.833333334 Combine like terms: -1.833333334 + 1.833333334 = 0.000000000 0.000000000 + q = 1.536590744 + 1.833333334 q = 1.536590744 + 1.833333334 Combine like terms: 1.536590744 + 1.833333334 = 3.369924078 q = 3.369924078 Simplifying q = 3.369924078Subproblem 2
q + -1.833333334 = -1.536590744 Simplifying q + -1.833333334 = -1.536590744 Reorder the terms: -1.833333334 + q = -1.536590744 Solving -1.833333334 + q = -1.536590744 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '1.833333334' to each side of the equation. -1.833333334 + 1.833333334 + q = -1.536590744 + 1.833333334 Combine like terms: -1.833333334 + 1.833333334 = 0.000000000 0.000000000 + q = -1.536590744 + 1.833333334 q = -1.536590744 + 1.833333334 Combine like terms: -1.536590744 + 1.833333334 = 0.29674259 q = 0.29674259 Simplifying q = 0.29674259Solution
The solution to the problem is based on the solutions from the subproblems. q = {3.369924078, 0.29674259}Solution
q = {3.369924078, 0.29674259}
| 7x-3(5x-(5+x))=1-4x | | 3(w+15)= | | 9z+14z+-17=6 | | x-4=10/3 | | -4n=25 | | (r+3)-5=-4 | | 3x-5+9x=9x+15+36 | | 6+(6-2)+6= | | (r+3)-5=4 | | (5x-7)/3=6 | | -10=5w(2w-4) | | -w^2+7w-12=0 | | -2.1v-2.3=1.2+4.3 | | 2.4=0.8x+3.2 | | 1/3x-2/3=0 | | 5+3x-9=6x-4 | | x=75p+3550 | | 3n+7n=0 | | (K-1)(k-6)= | | S-8/2=3 | | 3(x)-7=83 | | 0=-w^2+4w-3 | | 10t-22=-5(-2t+3) | | -2w=-3w-7 | | 2/3x+3/4=3/5(x-5/8) | | 5(2x+3)-6+6-3(3x-1)-8=x+10 | | 4n-2.8=6.8 | | 10x+4=6x+8 | | 2x^2+23x-9.5=0 | | 0.06x=0.036 | | 2m+8.1=16.5 | | -3(4p+5)=-99 |